Practices of Co-censorship: The Bilateral Control of Italian-Yugoslavian Co-productions - Di Chiara, Francesco; Noto, Paolo (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
This paper investigates the connections between the film censorship systems of Italy and Yugoslavia, two countries that in the post-war years had different political and economic structures, but were involved in frequent collaborations that were first formalized in the co-production agreements signed in 1957. The underlying hypothesis is that censorship functions as both a repressive and enabling agency, insofar as it facilitates the negotiation of cultural, industrial, and ideological issues. Archival documents preserved in Rome and Belgrade, namely those of the Direzione Generale dello Spettacolo and the Savezna Komisija za Pregled Filmova, the bodies responsible for censorship in the respective countries, are used to reconstruct the cases of film made in collaboration between Italy and Yugoslavia and that therefore passed through the control of the authorities of both countries, such as Kapo (Gillo Pontecorvo, 1961), The Great War (Mario Monicelli, 1959) and War and Peace (King Vidor, 1956).